LITERATURE REVIEW : PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP RISIKO KECELAKAAN KARYAWAN DI EKSPEDISI - Putri Dwita Aprilia (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
All entities cannot meet their own needs, so the need for goods transportation services will continue throughout human civilization. the need for transportation of goods between locations that can be served by shipping companies. Of course, business actors engaged in transportation services or what are commonly referred to as shipping companies face many difficulties, especially with regard to the main business activities in this industry which are not related to transportation and are beyond the control of the owner. The purpose of this research is to conduct a thorough literature review on how occupational health and safety affects the likelihood of accidents involving expedition personnel. In this investigation, data and findings from relevant previous studies in the area will be collected, analyzed and synthesized. The literature review method is the one used in this paper for this study. The following steps are selecting appropriate journals, selecting keywords, searching for relevant literature, selecting relevant literature based on inclusion and exclusion criteria, analyzing data, materials, and writing document reviews. Ten articles on the impact of occupational health and safety on the risk of work accidents for expedition personnel were found after searching through various academic databases. Based on the findings of the data collection, transportation service providers must seriously implement risk management in order to reduce or even completely eliminate losses caused by risks that develop during the shipping process in the company's business operations